Synthetic Strategies for the Selective Functionalization of Carbon Nanodots Allow Optically Communicating Suprastructures - Bartolomei, Beatrice; Sbacchi, Maria; Rosso, Cristian; Günay-Gürer, Ayse; Zdrazil, Lukas; Cadranel, Alejandro; Kralj, Slavko; Guldi, Dirk Michael; Prato, Maurizio (Angewandte Chemie International Edition, 2024)
The surface of Carbon Nanodots (CNDs) stands as a rich chemical platform, able to regulate the interactions between particles and external species. Performing selective functionalization of these nanoscale entities is of practical importance, however, it still represents a considerable challenge. In this work, we exploited the organic chemistry toolbox to install target functionalities on the CND surface, while monitoring the chemical changes on the material's outer shell through nuclear magnetic resonance spectroscopy. Following this, we investigated the use of click chemistry to covalently connect CNDs of different nature en-route towards covalent suprastructures with unprecedent molecular control. The different photophysical properties of the connected particles allowed their optical communication in the excited state. This work paves the way for the development of selective and addressable CND building blocks which can act as modular nanoscale synthons that mirror the long-established reactivity of molecular organic synthesis.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Carbon Nanodots; Click Chemistry; Nanotechnology; Particle Network; Self-Assembly